Lens strengthening and antifogging production method
By dripping the reinforcement liquid and anti-fog liquid, combined with baking and plasma treatment, hardened wear-resistant hydrophilic anti-fog lenses are formed, which solves the problem of poor anti-fog effect of existing lenses and achieves stronger anti-fog performance and lens durability.
Patent Information
- Application Number
- CN202411889416.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing anti-fog lenses have poor comfort and durability, resulting in poor strength and anti-fog effect of the lenses, which cannot meet the needs of use.
The reinforcement liquid and anti-fog liquid are applied driply, and hardened wear-resistant hydrophilic anti-fog lenses are formed during baking and plasma treatment.
It realizes the strengthening and anti-fog function of the lens surface, effectively prevents water vapor from condensing, maintains the clarity of the lens, improves the quality of the field of view, and enhances the bonding force between the anti-fog layer and the lens substrate, making it more durable.
Smart Images

Figure CN119588594A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lens processing, and in particular to a lens strengthening and anti-fogging production method. Background Art
[0002] Optical lenses refer to lenses with high light transmittance that are made of optical glass through multiple processing steps. In daily life, people have experienced this: when the room temperature drops below the atmospheric dew point, the glass surface will be covered with a layer of fog, making the glass blurry. This is because the moisture in the atmosphere attaches to the surface of the object to form very fine droplets, causing the light to be reflected randomly. These droplets will refract and scatter the light, changing the optical properties of the lens and affecting the light transmittance, thus bringing many inconveniences to life.
[0003] In order to avoid fog droplets on the lenses, existing anti-fog lenses generally adopt an anti-fog coating (immersion anti-fog coating) and other coatings for combined processing. Although this method can achieve a certain anti-fog effect, its structure and process have certain defects, and its comfort and durability are poor, resulting in poor strength and anti-fog effect of the lenses, and cannot better meet the use requirements.
[0004] In view of this, the present application aims to provide a lens strengthening and anti-fogging production method to better solve the above-mentioned technical problems. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a lens strengthening and anti-fogging production method, which forms a hardened, wear-resistant, hydrophilic anti-fogging lens through strengthening and anti-fogging processing, which can better meet the use requirements.
[0006] The technical solution adopted by the present invention is:
[0007] A lens strengthening and anti-fogging production method comprises the following steps:
[0008] S1. Fix the lens with a lens clamp, use an oil gun to drip strengthening liquid on the inside of the lens, shake it to evenly spread a layer of strengthening liquid on the inside of the lens, and absorb the excess strengthening liquid to prevent the strengthening liquid from accumulating. Then put the lens into the oven and pre-dry it at 70-100℃ to preliminarily harden the surface of the strengthening layer;
[0009] S2. The pre-dried lens is sent to an oven and baked at 100-130°C. After baking, the lens is taken out and cooled at room temperature;
[0010] S3. Place the cooled lens with the anti-fog surface facing downward on the plasma treatment tray, then insert the tray into the slot of the plasma machine, and start the equipment for plasma treatment under a mixed gas of oxygen and argon;
[0011] S4. Use an oil dropper to drip anti-fog liquid on the inner side of the lens after plasma treatment, shake it to evenly spread a layer of anti-fog liquid on the inner side of the mirror, and absorb the excess anti-fog liquid to prevent it from overflowing. Then put the lens into the oven and dry it at 60-100℃. After baking, take out the lens, cool it at room temperature, and then test and package it to complete the production and processing.
[0012] Furthermore, in step S1, the appearance of the lens needs to be checked before dripping the strengthening liquid and after pre-baking.
[0013] Furthermore, in step S1, an air gun is used to remove dust from the lens before dripping the strengthening liquid.
[0014] Furthermore, in step S1, the time for dripping the strengthening liquid using the oil dripping gun is set to 0.2-1 second according to the size of the lens.
[0015] Furthermore, in step S1, the pre-drying time of the lens in the oven is set to 5-15 minutes.
[0016] Furthermore, in step S2, the lens is baked in the oven for 60-180 minutes, and cooled at room temperature for no less than 30 minutes.
[0017] Furthermore, in step S3, the cooled lens needs to be plasma treated within 7 days.
[0018] Furthermore, in step S3, the plasma treatment equipment uses a radio frequency power supply, the power of the plasma treatment is set to 200-300W, the vacuum degree of the plasma treatment equipment is 15-25Pa, the ratio of oxygen and argon passing through is 3:1, the flow rate of oxygen and argon is 30-90sccm, and the plasma treatment time is 120-300 seconds.
[0019] Furthermore, in step S4, the time for dripping the anti-fog liquid using the oil dripping gun is set to 0.2-1s.
[0020] Furthermore, in step S4, the baking time of the lens is 45-150 minutes.
[0021] Furthermore, in step S1, the added strengthening liquid is a hardening silicone resin coating agent.
[0022] Furthermore, in step S4, the anti-fog liquid added is a wear-resistant hydrophilic anti-fog oil, and the main component of the wear-resistant hydrophilic anti-fog oil is: sodium N,N-dimethyl-dihydroxypropane sulfonate, which is prepared by the following specific steps:
[0023] 1) Dissolve 10 parts by weight of sodium N,N-dimethyl-dihydroxypropane sulfonate in 40 parts of deionized water at 50-80° C., mix and stir for 6-12 hours to obtain a sodium N,N-dimethyl-dihydroxypropane sulfonate solution;
[0024] 2) 5-10 parts of γ-hydroxypropyltrimethoxysilane, 5-10 parts of nano-SiO 2 , 5-10 parts of TiO 2 , 1-10 parts of modified silicone oil are added into 60 parts of deionized water at 60-100°C, and the mixture is fully mixed and stirred for 6-8 hours to obtain a multi-substance mixed solution;
[0025] 3) Mix the above multi-substance mixed solution and N,N-dimethyl-dihydroxypropane sulfonate sodium solution together, heat to 60-100°C, stir thoroughly for 4-10 hours, and then heat treat at 60-100°C for 2-5 hours to fully combine the substances.
[0026] 4) Add 5-10 parts of methanol to the fully combined solution, stir at room temperature for 10-12 hours, let stand for 4-10 hours after stirring for defoaming treatment, and filter with 500-800 mesh filter paper after defoaming to obtain wear-resistant hydrophilic anti-fog oil.
[0027] The beneficial effects of the present invention are as follows:
[0028] The lens strengthening and anti-fog production method provided by the present invention forms a thin film with strengthening and anti-fog functions on the lens surface through dripping and baking treatment of strengthening liquid and anti-fog liquid, forming a hardened, wear-resistant, hydrophilic anti-fog lens, which can effectively prevent water vapor from condensing into water droplets on the lens surface, and can maintain the clarity of the lens and improve the visual field quality even in an environment with large temperature differences and high humidity. At the same time, the lens surface treated with plasma during the production process has a stronger bonding force between the anti-fog layer and the lens substrate, and is not easy to fall off or fail, which ensures the durability of the anti-fog performance and reduces the trouble of users having to frequently replace or maintain the lenses during use. The lens strengthening and anti-fog production method provided by the present application not only improves the durability and anti-fog performance of the lenses, but also improves the production efficiency and quality control level, and the produced lenses can better meet the use needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a process flow chart in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively by way of examples, and preferred embodiments of the present invention are given below. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. Any other implementation schemes obtained by modifying or equivalently replacing the technical scheme of the present invention without creative results are within the protection scope of the present invention.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for describing specific embodiments and are not intended to limit the present invention.
[0032] The numerical values disclosed in the embodiments of the present invention are approximate values, not definite values. When the error or experimental conditions permit, all values within the error range may be included without being limited to the specific numerical values disclosed in the embodiments of the present invention.
[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0034] The following are specific embodiments:
[0035] like Figure 1 As shown, this embodiment provides a lens strengthening and anti-fogging production method, comprising the following steps:
[0036] S1. Fix the lens with a lens clip, use an oil gun to drip strengthening liquid on the inner side of the lens, shake it to evenly spread a layer of strengthening liquid on the inner side of the lens, and absorb the excess strengthening liquid to prevent the strengthening liquid from accumulating. Then put the lens into the oven and pre-dry it at 70-100℃ for 5-15 minutes to preliminarily harden the surface of the strengthening layer;
[0037] Specifically, after the lens is clamped and fixed, check whether there are scratches, pits and other appearance defects, then use an air gun to remove dust from the lens. During the process of dripping the strengthening liquid, set the dripping time of the strengthening liquid to 0.2-1 second to ensure that the strengthening liquid covers the entire anti-fogging surface of the lens, and pay attention to the strengthening liquid not overflowing outside the lens cup. If overflowing, scrap it. In the process of sucking away the excess strengthening liquid, you can repeat the suction once based on the suction situation to prevent the problem of strengthening liquid accumulation;
[0038] In addition, during the dripping process of the strengthening liquid, confirm that the solid content of the strengthening liquid is 22-28%, the viscosity is 5-10pas, the workshop temperature is 22±2℃, and the humidity is less than 50%;
[0039] S2. The pre-dried lens is sent to the oven and baked at 100-130°C for 60-180 minutes. After baking, the lens is removed and cooled at room temperature for more than 30 minutes;
[0040] S3. Place the cooled lens with the anti-fog surface facing downward on the plasma treatment tray, then insert the tray into the slot of the plasma machine, and start the equipment for plasma treatment under a mixed gas of oxygen and argon;
[0041] Specifically, the cooled lens needs to be plasma treated within 7 days. The plasma treatment equipment uses a radio frequency power supply. The power of the plasma treatment is set to 200-300W. The vacuum degree of the plasma treatment equipment is 15-25Pa. The ratio of oxygen and argon passing through is 3:1. The flow rate of oxygen and argon is 30-90sccm. The plasma treatment time is 150-300 seconds.
[0042] S4. Use an oil dropper to drip anti-fog liquid on the inner side of the lens after plasma treatment, shake it to evenly spread a layer of anti-fog liquid on the inner side of the lens, and absorb the excess anti-fog liquid to prevent the anti-fog liquid from overflowing. Then put the lens into a drying oven and dry it at 60-100℃ for 60-180min. After baking, take out the lens, cool it at room temperature, and then test and package it to complete the production and processing;
[0043] Specifically, before dripping the anti-fog liquid, check whether there are scratches, pitting and other poor appearance. During the dripping process of the anti-fog liquid, set the timer to 0.2-1 second to ensure that the anti-fog liquid covers the entire anti-fog surface of the lens. The anti-fog liquid should not overflow beyond the lens cup. The anti-fog liquid cannot flow back when draining the oil in the lens. If there is backflow or overflow, or it flows to the outer mirror surface, the lens will be scrapped. In the process of absorbing excess anti-fog liquid, the lens with the anti-fog liquid dripped on it will be tilted, and the oil absorption position will be slightly lower. Based on the absorption situation, the absorption can be repeated once to prevent the anti-fog liquid from flowing back.
[0044] Specifically, the oil dripping gun used in this embodiment is a self-gravity automatic oil dripping machine, and the negative pressure oil suction bottle is used in the liquid suction process.
[0045] Specifically, in this embodiment, the lens body is made of polycarbonate (PC), the added strengthening liquid is a hardened silicone resin coating agent, which is a commercially available strengthening liquid for lenses, so as to play a hardening and strengthening role; the added anti-fog liquid is a wear-resistant hydrophilic anti-fog oil, which is a special combination. Specifically, the main component of the wear-resistant hydrophilic anti-fog oil is: N, N-dimethyl-dihydroxypropane sulfonate sodium, which is prepared by the following specific steps:
[0046] 1) Dissolve 10 parts by weight of sodium N,N-dimethyl-dihydroxypropane sulfonate in 40 parts of deionized water at 70° C., mix and stir for 10 hours to obtain a sodium N,N-dimethyl-dihydroxypropane sulfonate solution;
[0047] 2) 8 parts of γ-hydroxypropyltrimethoxysilane, 8 parts of nano-SiO 2 , 7 parts of TiO 2 , 1-10 parts of modified silicone oil are added into 60 parts of deionized water at 85°C, and the mixture is fully mixed and stirred for 7 hours to obtain a multi-substance mixed solution;
[0048] 3) The above multi-substance mixed solution and the sodium N,N-dimethyl-dihydroxypropane sulfonate solution were mixed together, heated to 90°C, stirred for 8 hours, and then heat treated at 85°C for 3.5 hours to fully combine the substances.
[0049] 4) Add 8 parts of methanol to the fully combined solution, stir at room temperature for 11 hours, let stand for 8 hours after stirring for defoaming treatment, and filter with 600 mesh filter paper after defoaming to obtain wear-resistant hydrophilic anti-fog oil.
[0050] In the wear-resistant hydrophilic anti-fog oil, N, N-dimethyl-dihydrohydroxypropane sulfonate is the main film-forming component, γ-hydroxypropyl trimethoxysilane is used to increase adhesion, and nano-SiO 2 and nano-TiO 2 Used to increase water resistance and hydrophilicity, the modified silicone oil is used to increase wear resistance and leveling, the methanol is used to increase solubility, and the water is used as a solution.
[0051] The lenses produced in this embodiment were tested for water drop angle. Five lenses were taken for parallel testing. The test results were all less than 5, indicating that the test was qualified.
[0052] The surface hardness of the anti-fog layer of the lens produced in this embodiment was tested. During the test, 5 lenses were taken and tested in parallel. The test results all reached the pencil hardness level H, and the test was qualified.
[0053] The lenses produced in this embodiment were subjected to a hundred-grid test on the surface of the anti-fog layer. During the test, 5 lenses were taken and tested in parallel. The test results all reached level 0 or level 1, and the test was qualified.
[0054] The lenses produced in this embodiment were subjected to a linear friction test on the surface of the anti-fog layer. During the test, 5 lenses were taken and tested in parallel (with a wet friction cloth at a pressure of 500 g). The wet test was performed 25 times. There was no scratch on the surface of the anti-fog layer, and the test was qualified.
[0055] The lenses produced in this embodiment were subjected to an anti-fog layer anti-fog cycle test (simulating the state of actual use by swimmers). During the test, 5 lenses were taken. If they could remain fog-free for more than 10 times in an inactive state (activation method: immersing the goggles in water and rubbing the anti-fog layer with the fingertips for 5 seconds), and remain fog-free for more than 100 times after activation, the test was qualified.
[0056] It can be seen that the lens surface prepared in this embodiment has good wetting properties and anti-fog effect, and can provide users with a clearer and more comfortable visual experience, thereby better meeting application scenarios such as daily life, outdoor sports, and medical fields.
[0057] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A lens strengthening and anti-fogging production method, characterized in that: The steps include: S1. Fix the lens with a lens clamp, use an oil gun to drip strengthening liquid on the inside of the lens, shake it to evenly spread a layer of strengthening liquid on the inside of the lens, and absorb the excess strengthening liquid to prevent the strengthening liquid from accumulating. Then put the lens into the oven and pre-dry it at 70-100℃ to preliminarily harden the surface of the strengthening layer; S2. The pre-dried lens is sent to an oven and baked at 100-130°C. After baking, the lens is taken out and cooled at room temperature; S3. Place the cooled lens with the anti-fog surface facing downward on the plasma treatment tray, then insert the tray into the slot of the plasma machine, and start the equipment for plasma treatment under a mixed gas of oxygen and argon; S4. Use an oil dropper to drip anti-fog liquid on the inner side of the lens after plasma treatment, shake it to evenly spread a layer of anti-fog liquid on the inner side of the mirror, and absorb the excess anti-fog liquid to prevent it from overflowing. Then put the lens into the oven and dry it at 60-100℃. After baking, take out the lens, cool it at room temperature, and then test and package it to complete the production and processing.
2. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S1, the appearance of the lens needs to be checked before dripping the strengthening liquid and after pre-baking.
3. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S1, the lens needs to be dusted using an air gun before dripping the strengthening liquid.
4. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S1, the time for dripping the strengthening liquid using the oil dripping gun is set to 0.2-1s according to the size of the lens.
5. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S1, the pre-drying time of the lens in the oven is set to 5-15 minutes; in step S2, the baking time of the lens in the oven is 60-180 minutes, and the cooling time at room temperature is not less than 30 minutes.
6. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S3, the cooled lens needs to be plasma treated within 7 days.
7. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S3, the plasma treatment equipment uses a radio frequency power supply, the power of the plasma treatment is set to 200-300W, the vacuum degree of the plasma treatment equipment is 15-25Pa, the ratio of oxygen and argon passing through is 3:1, the flow rate of oxygen and argon is 30-90sccm, and the plasma treatment time is 120-300 seconds.
8. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S4, the time for dripping the anti-fog liquid using the oil dripping gun is set to 0.2-1s.
9. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S4, the lens is baked for 45-150 minutes.
10. The lens strengthening and anti-fogging production method according to claim 1, characterized in that: In step S1, the added strengthening liquid is a hardened silicone resin coating agent; In step S4, the anti-fog liquid added is a wear-resistant hydrophilic anti-fog oil, the main component of which is: sodium N,N-dimethyl-dihydroxypropane sulfonate, which is prepared by the following specific steps: 1) Dissolve 10 parts by weight of sodium N,N-dimethyl-dihydroxypropane sulfonate in 40 parts of deionized water at 50-80° C., mix and stir for 6-12 hours to obtain a sodium N,N-dimethyl-dihydroxypropane sulfonate solution; 2) adding 5-10 parts of γ-hydroxypropyltrimethoxysilane, 5-10 parts of nano-SiO2, 5-10 parts of TiO2, and 1-10 parts of modified silicone oil to 60 parts of deionized water at 60-100° C., and mixing and stirring for 6-8 hours to obtain a multi-substance mixed solution; 3) Mix the above multi-substance mixed solution and N,N-dimethyl-dihydroxypropane sulfonate sodium solution together, heat to 60-100°C, stir thoroughly for 4-10 hours, and then heat treat at 60-100°C for 2-5 hours to fully combine the substances. 4) Add 5-10 parts of methanol to the fully combined solution, stir at room temperature for 10-12 hours, let stand for 4-10 hours after stirring for defoaming treatment, and filter with 500-800 mesh filter paper after defoaming to obtain wear-resistant hydrophilic anti-fog oil.
Citation Information
Patent Citations
Glasses fogging-preventing and cleaning solution and preparation method thereof
CN107937165A
Preparation process of hardened anti-fog lens
CN111323851A
Anti-fog lens and preparation method thereof
CN119060394A
Plasma treatment apparatus and plasma treatment method
TW201824332A
Plasma treatment apparatus and plasma treatment method
US20180187310A1